Low Prevalence of Legal Protection Among the Elderly With Neurocognitive Disorders in France - Koskas, Pierre; Hounkonnou, Cornélia P A; Couffignal, Camille (Alzheimer disease and associated disorders, 2025)
The prevalence of major neurocognitive disorders (MNCD) increases to 30% after 80 years of age. Vulnerability often goes unnoticed for a long time, and patients are seldom subject to legal protection (LP), creating an ethical and legal dilemma. The French National Alzheimer's Database (BNA) is a national network set up in 2005 to collect data on neurocognitive disorders from all memory clinics in France. Data extraction from the BNA in 2022 produced a sample of 1,187,199 patients. We retained 795,953 patients, with a mean age of 78 years, and approximately two-thirds of the patients were women. We excluded patients with no medical assessment (n=135,810), without MNCD (n=237,209), birth year ≥1981 (n=18,189), and consultation date <2005 (n=38). A total of 32,593 patients (4.09%) have had LP during the 15-year study period. They have lower MMSE scores than others (17.9±6.6 vs. 20.6±6.5 P<0.01), more likely to live alone (45.25% vs. 36,1% P<0.01) or at nursing home (22.83% vs. 8.35% P<0.01). The low prevalence of LP among persons with MNCD emphasizes the potential vulnerability and legal risk of this group.